2011
DOI: 10.1017/s1368980011001297
|View full text |Cite
|
Sign up to set email alerts
|

Re-imagining the ‘social’ in the nutrition sciences

Abstract: Objective: In response to The New Nutrition Science Project's Giessen Declaration, we provide here a case for a more fully described and integrated 'social' dimension within the nutrition sciences. Design: This paper explores what we mean when we argue for socially engaged nutrition sciences (SENS), and describes the disciplinary fields, epistemologies and methodologies that contribute to SENS' potential rich diversity and value. Additionally, the current positioning of 'social nutrition' research within the n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
37
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(38 citation statements)
references
References 52 publications
(74 reference statements)
0
37
0
1
Order By: Relevance
“…Anthony Giddens, social theorist, suggests that there is tension between individual and structural approaches and that human activity is produced by personal agency but is also responsive to and influenced by structural elements of the social world (33,34) . This suggests that a 'both-and' approach should be the basis for action in this setting, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Anthony Giddens, social theorist, suggests that there is tension between individual and structural approaches and that human activity is produced by personal agency but is also responsive to and influenced by structural elements of the social world (33,34) . This suggests that a 'both-and' approach should be the basis for action in this setting, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Relevant competencies: CC3c, CC3e, CC3f The participants (2)(3)(4)(5)(6)(7)(8) suggested that organising and structuring their lives was important to ensure adherence (nine references) and that when that structure was challenged, adherence became difficult. A lack of structure, organisation and time management led to previous failures for some:…”
Section: Self-managementmentioning
confidence: 99%
“…Some participants revealed that stressful life events led to binge eating in the absence of sufficient coping mechanisms and comfort eating was problem for some. Social situations were revealed unanimously to threaten consistency (1)(2)(3)(4)(5)(6)(7)(8) and the following examples were described as coping mechanisms for such occasions: driving instead of drinking, limiting food choices, flexible restraint and increasing exercise:…”
Section: Relevant Competencies: Cc3c Cc3fmentioning
confidence: 99%
See 1 more Smart Citation
“…In a final article to highlight in this issue, Schubert et al (9) remind us of what Leitzmann and Cannon (10) declared in this journal six years ago, as part of the New Nutrition Science: 'the main solutions to nutritional problems lie less in unlocking biological pathways, and more in creating healthy societies and also environments'. Schubert et al's objectives are to promote a central role for a 'social' dimension in the nutrition sciences and to encourage greater social engagement by nutrition r The Authors 2012 researchers.…”
mentioning
confidence: 99%